1, 1, 1, 2-tetrafluoroethane photofragmentation: a translational kinetic energy release analysis in the EUV and X-ray energies range. (18th July 2022) - Bonfim, Víctor S. A.; Prazeres, Italo; Morcelle, Viviane; Marinho, Ricardo R. T.; Arruda, Manuela S.; Mendes, Luiz A. V.; Ribeiro, Leonardo C.; Santos, Mabele J.; Medina, Aline; Santos, Antônio C. F.
Abstract : A molecule with two or more atoms of the same element in distinct chemical environments is a trial system for probing site-specific fragmentation. In this context, special attention is deserved to 1, 1, 1, 2-tetrafluoroethane (CF3 CH2 F), which has been the subject of numerous studies. This work discusses the effects of extreme ultraviolet (EUV) and soft X-ray irradiation on CF3 CH2 F from a dedicated translational kinetic energy release (KER) perspective. This analysis is achieved by evaluating the mean KER for its fragments at photon energies over 30–320 eV and computing the KER distribution (KERD) for the main fragments over the 282–320 eV range. The questions of interest from the point of view of the present study are twofold: (i) How do the mean KER of ionic fragments of the valence or core-excited CF3 CH2 F molecule change as a function of incident photon energy? (ii) Is there any evidence of site-specific or state-specific dissociation mechanisms in a molecule containing two carbon atoms in distinct chemical environments? From our results, lighter fragments showed to have their mean KER virtually following respective ion yields previously reported. And the overall learning is that the chemical environment associated with each C 1s excitation plays a role in differentiating the KER results. GRAPHICAL ABSTRACT: UF0001